Analisis massive open online course zonainformatika.com menggunakan technology acceptance model - Atmojo, Suryo; Dewi, Suzana; Widhiyanta, Nurwahyudi; Wulansari, Laily Alfina; Utami, Ruli (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2025)
This analysis set out to assess user acceptance of the zonainformatika.com massive open online course application, applying the Technology Acceptance Model. The study included 125 registered users and covered 48 available course roadmaps. The approach involved collecting user statistical data, specifically looking at roadmap completion rates and user satisfaction levels. We used descriptive analysis to understand user behavior patterns and how satisfied users were with the platform. The results revealed that 65% of users completed at least one roadmap. The average time spent per learning session was 45 minutes. Furthermore, 88% of users stated they were satisfied or very satisfied with the application. These findings indicate that users generally accept the massive open online course application. This is supported by the high number of users completing courses and their reported satisfaction. This analysis provides useful understanding for the application's developers. The information can help them improve features and services to make the learning experience better for users. The study's outcomes can also be a resource for tutors, offering knowledge about the psychological factors influencing users of massive open online courses. This may help tutors create learning assessments that fit user needs. Additionally, the findings may guide the development field by encouraging new ideas in building massive open online course applications.